2020
DOI: 10.1007/s11250-020-02244-3
|View full text |Cite
|
Sign up to set email alerts
|

Shading effect on physiological parameters and in vitro embryo production of tropical adapted Nellore heifers in integrated crop-livestock-forest systems

Abstract: The aim of this study was to evaluate the impact of increased shadow supply in integrated crop-livestock-forest systems on in vitro embryonic development and physiological parameters related to stress response in Nellore heifers (Bos indicus). For the study, animals (n = 16) were randomly divided into two groups and kept in areas with different afforestation systems, the integrated crop-livestock-forest (ICLF) and the integrated crop-livestock (ICL) system. The microclimate of the ICLF system provided better c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
4
1
7
Order By: Relevance
“…However, specific mechanisms of subsequent laboratory steps should be studied to elucidate the equivalent blastocyst rates on D7 from cows raised on shaded or unshaded pastures (42.9 vs 35.9%). This was in contrast to previous results in which an increase in the rate of blastocysts was observed in Nellore heifers raised in the SP system 45 . However, during the summer, lower numbers of total oocytes, viable oocytes, recovery rate, cleaved structures, cleavage rate, and blastocysts on day 7 were observed, evidencing the deleterious effect of warmer seasons on fertility, as previously reported 45 , 46 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, specific mechanisms of subsequent laboratory steps should be studied to elucidate the equivalent blastocyst rates on D7 from cows raised on shaded or unshaded pastures (42.9 vs 35.9%). This was in contrast to previous results in which an increase in the rate of blastocysts was observed in Nellore heifers raised in the SP system 45 . However, during the summer, lower numbers of total oocytes, viable oocytes, recovery rate, cleaved structures, cleavage rate, and blastocysts on day 7 were observed, evidencing the deleterious effect of warmer seasons on fertility, as previously reported 45 , 46 .…”
Section: Discussioncontrasting
confidence: 99%
“…Our research group demonstrated some examples of how biological systems react to the adaptation process. For example, we showed that different tropical breeds [ 92 ] respond differently to the “stress” they are subjected to, especially under different housing conditions [ 93 ]. Additionally, the duration and intensity of in vitro thermal stress [ 94 ] exhibited an interesting pattern of oocyte and embryo development after maturation under cold and high temperatures.…”
Section: Heat Stressmentioning
confidence: 99%
“…Therefore, reproductive biotechnologies are generally not performed in beef cattle during hot months. One alternative might be to use frozen embryos, as demonstrated for dairy cattle [ 177 ] or to use breeds more resistant to heat stress, such as Nellore [ 178 ].…”
Section: Beef Cattle Stress and Reproductive Biotechnologiesmentioning
confidence: 99%